Strengthening Student Religious Character Education Through ROHIS Extracurricular Activities at SMKN 10 Bandung - Lesti Sahita Khairunisa; Rif’at Hafidz Al Asyad; Muhammad Aditya Firdaus (al-Afkar, Journal For Islamic Studies, 2023)
This research is motivated by the decline in student morality. In the midst of the inability of school education institutions to overcome the moral decadence above, there are schools that consistently implement character education continuously, namely SMK N 10 Bandung through spiritual extracurricular activities. The purpose of this study was to determine the strengthening of students' religious character education through Spiritual extracurricular activities at SMK Negeri 10 Bandung. This type of research is descriptive qualitative. The research instruments used were interviews, observation, and documentation. The research data were analyzed with the stages of data reduction, data presentation, and drawing conclusions. The results of this study indicate that: 1) There are several spiritual extracurricular programs in improving religious character at SMK Negeri 10 Bandung culture 5 S, Implementation of religious programs reading asmaul husna in congregation, support, rewards, as well as rules and regulations. 2) Implementation of the Rohis extracurricular at school is carried out once a week, namely on Fridays and has a positive effect on the development of SMK Negeri 10 Bandung. 3) Supporting factors include facilities and infrastructure, the encouragement of the school principal and school members, the human need for religion. The inhibiting factors include time, awareness and enthusiasm, moral support from the family and environmental influences, The timing of activities that clash with intracurricular activities of each departement. 4) Spiritual extracurriculars are effective in developing the religious character of students at SMK N 10 Bandung.